Outcome Prediction by Quantitative Right Ventricular Function Assessment in 575 Subjects Evaluated for Pulmonary Hypertension - Fine, Nowell M.; Chen, Libo; Bastiansen, Paul M.; Frantz, Robert P.; Pellikka, Patricia A.; Oh, Jae K.; Kane, Garvan C. (Circulation. Cardiovascular imaging, 2013)
Although right ventricular (RV) dysfunction is a major determinant of outcome in patients with pulmonary hypertension (PH), the optimal measure of RV function is poorly defined. We hypothesized that RV strain measured by speckle-tracking echocardiography predicts outcome in PH over a broad range of pulmonary pressures. Prospective peak RV longitudinal systolic strain measurement was performed on 575 patients (mean age, 56 ± 18 years; 63% women) referred for echocardiography for known or suspected PH. Survival status was assessed over a median of 16.5 (interquartile range, 7.6-20.0) months. There were 406 patients with PH (71%) (74% group 1, 14% group 3, and 12% group 4) and 169 patients without evidence of PH (29%). Among patients with PH, 46% were World Health Organization functional class III-IV. The mean RV strain was -21.2 ± 6.7% for all patients. RV strain declined with worse functional class, shorter 6-minute walk distances, higher N-terminal pro-B-type natriuretic peptide levels, and the presence of right heart failure. RV strain predicted outcome across pulmonary pressures and groups of PH. Eighteen-month survival was 92%, 88%, 85%, and 71% according to RV strain quartile (P<0.001), with a 1.46 higher risk of death (95% confidence interval, 1.05-2.12) per 6.7% decline in RV strain. RV strain predicted survival when adjusted for pulmonary pressure, pulmonary vascular resistance, and right atrial pressure and provided incremental prognostic value over conventional clinical and echocardiographic variables. Quantitative assessment of RV free-wall systolic strain is feasible and is a powerful predictor of the clinical outcome of patients with known or suspected PH.